Highly chemoselective catalytic system for hydrogenation of diketones to ketols: an environmentally benevolent system - Deshmukh, Amit A.; Kinage, Anil K.; Kumar, Rajiv (Catalysis Letters, 2008)
Ru(Phen)(2)Cl-2 [Phen = Phenanthroline] anchored in organo-functionalized MCM-41 [Ru(Phen)(2)Cl-NH-MCM-41] efficiently catalyzes highly chemoselective hydrogenation of diketones to ketols (Sel. similar to 99%) under environmentally benign tri-phasic (solid-liquid-liquid) reaction condition in aqueous medium.
Keywords: Chemoselective; dione; Hydrogenation; ketol; ruthenium phenanthroline; Water

Highly selective synthesis of mono-ethylene glycol phenyl ethers via hydroxyalkoxylation of phenols by cyclic carbonates using large pore zeolites - Kinage, Anil K.; Gupte, Sunil P.; Chaturvedi, Rajiv K.; Chaudhari, Raghunath V. (Catalysis Communications, 2008)
Hydroxyalkoxylation of phenols by cyclic carbonates catalyzed by alkali loaded large pore zeolites has been reported. The study shows that KL type zeolite was recyclable and selective in producing mono-ethylene glycol pheryl ethers in similar to 98.5% yield. Various substituted simple phenols were converted into mono-ethylene glycol ether of phenols with over 90% yields, except 3-bromo and 2-methyl phenols. Mono hydroxyl plienols such as hydroquinone, biphenol and BPA (2,2-bis(4-hydroxyphenyl)propane) also produce corresponding mono- and di-ethylene glycol ethers. The ratio of ethylene carbonate to phenol was found to be critical for selective formation of monoethylene glycol phenyl ether of phenols. A ratio of two results in formation of appreciable amount of diether derivative viz., 2-(2-phenoxyethoxy) ethanol. Compared to ethylene carbonate, a lower reactivity of 1,2-propane carbonate was found for hydroxyalkoxylation of phenol. It was found that ring opening at less hindered methylene carbon of 1,2-propylene carbonate prevailed giving rise to selective formation of beta-hydroxy phenyl ethers. The reactivity of ethylene carbonate towards O-alkylation versus transesterification of phenol has been explained on the basis of HSAB concept. Finally, it has been shown that yield of mono-ethylene glycol phenyl ether is controlled both by basicity and channel architecture of zeolite structure. KL zeolite was found to be the most effective zeolite because of it's intermediate basicity and one dimensional channel architect. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: cyclic carbonate; ethylene glycol phenyl ether; hydroxyalkoxylation; phenol

Efficient heterogeneous catalytic system for chemoselective hydrogenation of unsaturated ketones in aqueous medium - Deshmukh, Amit A.; Kinage, Anil K.; Kumar, Rajiv; Meijboom, Reinout (Polyhedron, 2010)
A highly chemoselective and green heterogeneous catalytic system of immobilized Ru(II)-phenanthroline complexes on amino functionalised MCM-41 material for the chemoselective hydrogenation of unsaturated ketones to unsaturated alcohols is demonstrated using water as a solvent The XRD and FTIR spectra show the highly ordered hexagonal nature of the MCM-41 even after encapsulation of the ruthenium complex The complex retains its configuration after anchoring as was confirmed by FTIR and UV-Vis analysis The detailed reaction parametric effect was studied for the hydrogenation of 3 methylpent-3-en-2-one to achieve complete conversion up to >99% chemoselectivity of 3-methylpent-3-en-2 ol The anchored heterogeneous catalysts were recycled effectively and reused five times with marginal changes in activity and selectivity The use of water as a solvent not only afforded high activity for the hydroge nation reaction compared to organic solvents but also afforded a green process Crown Copyright (C) 2010 Published by Elsevier Ltd All rights reserved
Keywords: 1 10 Phenanthroline; alpha beta Unsaturated ketone; Chemoselective hydrogenation; mesoporous materials; ruthenium

Heterogenized Ru(II) phenanthroline complex for chemoselective hydrogenation of diketones under biphasic aqueous medium - Deshmukh, Amit A.; Kinage, Anil K.; Kumar, Rajiv; Meijboom, Reinout (Journal of Molecular Catalysis A-Chemical, 2010)
The chemoselective hydrogenation of acetylacetone to 4-hydroxypentan-2-one over immobilized ruthenium phenanthroline metal complexes in amino functionalized MCM-41 in biphasic aqueous reaction medium was investigated. The catalyst was characterized by XRD, TEM, surface analysis, FT-IR and UV-vis to understand the morphology, complex geometry, and XPS such that the oxidation state of the metal complex inside the MCM-41 framework could be understood. The use of water as a solvent, not only gives high activity and selectivity for hydrogenation of acetylacetone, but also gives a path for an environmentally safer process. The optimizations of ligand, metal to ligand ratio, the choice of solvent and other reaction parameters were studied in detail. The heterogeneous catalytic system gave a higher degree of chemoselectivity (99%) towards 4-hydroxypentan-2-one as compared to homogeneous catalyst when hydrogenation was carried out using water as a solvent. The immobilized ruthenium-phenanthroline complex was easily separated and reused. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: 4-Hydroxypentan-2-one; acetylacetone; Chemoselective; Diketone; Hydrogenation; Phenanthroline; ruthenium; Water

Ru(II) phenanthroline complex as catalyst for chemoselective hydrogenation of nitro-aryls in a green process - Deshmukh, Amit A.; Prashar, Atul K.; Kinage, Anil K.; Kumar, Rajiv; Meijboom, Reinout (Industrial & Engineering Chemistry Research, 2010)
Ru(II) Phenanthroline [Ru(II)(Phen)(n) where n = 1,2,3] complexes were used as highly chemoselective catalysts for hydrogenation of nitro aryls using molecular hydrogen in an aqueous media. Water, universal solvent, was used as a reaction mixture for hydrogenation of nitro-aryls to make the process green. The chemoselectivity in hydrogenation of substituted nitrobenzene to substituted aniline was obtained as high as >99% at about complete conversion of substituted nitrobenzene. The parametric effects, including effect of solvent, effect of ligand, effect of metal to ligand ratio, effect of temperature and pressure, were studied in detail to obtain the best results. The Ru(Phen)(n) was characterized by FTIR, UV-vis, and XPS.

Growth of hydrothermally stable meso-porous silica structure interconnected around micro-porous zeolite crystals - Kinage, Anil K.; Prashar, Atul K.; Berlier, Gloria; Chaturvedi, Rajiv K. (Materials Characterization, 2011)
The growth of hydrothermally stable ordered meso-porous silica with M41S type structure interconnected around zeolite crystals was achieved from seeds normally nucleating the crystallization of micro-porous zeolite. The solid state NMR and FT-IR showed species like Si(OSi)(3)OH and Si(OSi)(2)(OH)(2) (or Q(3) and Q(2) sites, respectively) are formed during first hydrothermal treatment with surfactant and NaOH. These species and surface silanol group of zeolite crystal condense to give meso-porous silica structure interconnected around zeolite crystal during re-crystallization at lower pH. Resulting meso-micro-porous hybrid material is found to be highly active, selective and stable in the synthesis of 2-(phenylamino) ethanol from aniline and ethylene carbonate compare to parent ZSM-5 and pure MCM-41. (C) 2011 Elsevier Inc. All rights reserved.
Keywords: Hydrothermal stability; Interconnected meso-porous silica; Meso-micro hybrid material; Synthesis of amino alcohol

Environmentally benign synthesis of beta-hydroxy sulfides using cyclic carbonates catalyzed by large-pore zeolites - Upare, Pravin P.; Kinage, Anil K.; Shingote, Savita K.; Gupte, Sunil P. (Green Chemistry Letters and Reviews, 2012)
An efficient one-pot synthesis of beta-hydroxy sulfides from thiophenol and cyclic carbonates catalyzed by large-pore zeolites has been reported. Reaction of thiophenol with ethylene carbonate in the presence of the Na-X zeolite catalyst gave the highest yield of 2-(phenylthio)ethanol (100%), while reaction with propylene carbonate a highest yield of regioselective product 1-(phenylthio)propan-2-ol was obtained (97%). Enantiomerically pure 1,2-propylene carbonate gave highly regioselective and stereospecific phenylthiopropanol, demonstrating that original chirality of propylene carbonate is retained. A plausible mechanism has been proposed for zeolite-catalyzed transformation involving a chemoselective nucleophilic attack of thiophenoloxide ion onto the less-substituted carbon of cyclic carbonate. The Na-X zeolite catalyst is recyclable and provides advantages of green chemistry approach to the synthesis of beta-hydroxy sulfides without the use of any solvent.
Keywords: beta-hydroxy sulfide; ethylene carbonate; propylene carbonate; thiophenol; zeolite

Chiral amino-acid-amide based ionic liquids as a stereoselective organocatalyst in asymmetric transfer hydrogenation of acetophenone at room-temperature - Javle, Balasaheb R.; Kinage, Anil K. (Chemistryselect, 2018)
Chiral Ionic Liquids (CILs) of amino acid amide were synthesized and used as novel organo catalyst for Asymmetric Transfer Hydrogenation (ATH) of acetophenone at room temperature. The developed CILs show very high yield and excellent enantio-selectivity in transfer hydrogenation of acetophenone.

Amino acid amide based ionic liquid as an efficient organo-catalyst for solvent-free knoevenagel condensation at room temperature - Burate, Pralhad A.; Javle, Balasaheb R.; Desale, Pranjal H.; Kinage, Anil K. (Catalysis Letters, 2019)
Ionic liquids of amino acid amide were synthesized and used as an efficient catalyst for solvent-free Knoevenagel condensation. Synthesized ionic liquids are an environmentally benign, inexpensive, metal free and plays the dual role of solvent as well as an efficient catalyst for Knoevenagel condensation. A wide range of aliphatic, aromatic and heteroaromatic aldehydes easily undergo condensation with malononitrile and ethyl cyanoacetate. The reaction proceeds at room temperature without using any organic solvent and is very fast with good to excellent yield. Additionally, the catalyst is easily separable and recyclable without loss of activity. [GRAPHICS] .
Keywords: Acrylonitrile; Amino acid amide; Cyanoacrylate; Ionic liquid; Knoevenagel condensation; Solvent-free

Organocatalysed one-pot three component synthesis of 3,3′-disubstituted oxindoles featuring an all-carbon quaternary center and [spiro 2H-pyran-3,4′-indoline] - Nichinde, Chandrakant B.; Patil, Baliram R.; Chaudhari, Suryakant S.; Mali, Bhupendra P.; Gonnade, Rajesh G.; Kinage, Anil K. (RSC Advances, 2023)
A simple and efficient methodology for the one-pot synthesis of 3,3 `-disubstituted oxindoles featuring an all-carbon quaternary center has been demonstrated through l-proline catalysed three-component reaction based on sequential Knoevenagel condensation/Michael addition and also one-pot synthesis of spiro[2H-pyran-3,4 `-indoline] through consecutive Knoevenagel condensation/Michael addition/reduction/cyclization reactions from readily available isatin derivatives, malononitrile, and ketones. The present methodology presents several advantages, including simple reaction set-up, short reaction times, and easy to work-up. Also, this strategy offers broad substrate scope with excellent yields and high atom economy, under mild reaction conditions.

Base controlled rongalite-mediated reductive aldol/cyclization and dimerization of isatylidene malononitriles/cyanoacetates - Chaudhari, Suryakant S.; Nichinde, Chandrakant B.; Patil, Baliram R.; Girase, Amardipsing S.; Rama Krishna, Gamidi; Kinage, Anil K. (Organic and biomolecular chemistry, 2024)
In this study, we developed a novel methodology involving a base-controlled, rongalite-mediated reductive/aldol reaction, followed by cyclization of isatylidene malononitriles/cyanoacetates, resulting in the synthesis of spiro[2,3-dihydrofuran-3,3 `-oxindole]. Additionally, we have disclosed a rongalite-mediated dimerization process for isatylidene malononitriles, yielding dispiro[cyclopent-3 `-ene]bisoxindole. The utilization of rongalite in this reaction serves a dual purpose, acting both as a reducing agent and a C1 synthon. The developed approach has several advantages like a simple reaction setup, a wide substrate scope, requiring less time, using water as a green solvent, no metal or catalyst is required and products can be easily isolated via filtration with excellent yields under mild reaction conditions. A novel methodology was developed for the synthesis of spiro[2,3-dihydrofuran-3,3 `-oxindole] and dispiro[cyclopent-3 `-ene]bisoxindole under mild reaction conditions using inexpensive reagents.

Organocatalyzed [4+2] cycloaddition of α,β-unsaturated ketones and isatylidene malononitrile: accessing spiro[3-arylcyclohexanone]oxindole derivatives - Patil, Baliram R.; Nichinde, Chandrakant B.; Chaudhari, Suryakant S.; Krishna, Gamidi Rama; Kinage, Anil K. (RSC Advances, 2024)
Herein, we developed a series of compounds featuring spiro[3-arylcyclohexanone]oxindoles through Barbas [4 + 2] cycloaddition reactions between isatylidene malononitrile and alpha,beta-unsaturated ketones using l-proline as an organocatalyst. The reported methodology offers many advantages such as mild reaction conditions, diverse substrate scope with high yields, easy reaction setup, and use of easily synthesizable starting materials. An l-proline catalyzed-Barbas-[4 + 2]-cycloaddition reaction is reported for the synthesis of spiro[3-arylcyclohexanone]oxindole derivatives. The method can tolerate a diverse substrate scope with high yields.

Reaction kinetics for catalytic hydrogenation of quinoline to decahydroquinoline as liquid organic hydrogen carrier - Bagwan, Farahanaz M.; Kinage, Anil K.; Vasireddy, Satyam Naidu (International Journal of Hydrogen Energy, 2024)
The catalytic hydrogenation of quinoline to decahydroquinoline (DHQ) formation is studied for various parameters such as temperature, hydrogen pressure, reaction time, solvents, reactant-to-solvent ratio, and catalyst loading over 5%Pd loaded on alumina (Pd/Al2O3) to obtain optimal reaction conditions. The hydrogen uptake of quinoline in the liquid phase reaction using isopropylalcohol (IPA) is studied in an autoclave reactor. The optimum reaction parameters of 50 bar H2 pressure and 175oC with reactant to solvent ratio of 1:9 for reaction time of 5 h are observed. The effect of IPA solvent showed that hydrogen uptake of 6.91 wt% with complete hydrogenation of quinoline and DHQ yield of more than 99% is observed. The reaction kinetic model is developed for a simplified reaction mechanism and is simulated using the Markov Chain Monte Carlo (MCMC) simulation tool to predict the rate constants and the experimental observations are validated with the model predictions. The activation energy for quinoline hydrogenation to py-THQ formation is estimated to be 136.57 kJ/mol. It is envisaged that quinoline hydrogenation to pz-THQ is the rate-limiting step in the DHQ formation.
Keywords: Decahydroquinoline (DHQ); Hydrogen uptake; Liquid organic hydrogen carrier (LOHC); Markov chain Monte Carlo (MCMC) simulation; Thermal screening unit (TSU); tool

Conjugate addition/cyclization of propanal with isatylidene malononitriles: an efficient one-pot organocatalytic approach for the synthesis of 3′-methyl spiro[2H-pyran-3,4′-indoline] - Patil, Baliram R.; Nichinde, Chandrakant B.; Girase, Amardipsing S.; Chaudhari, Suryakant S.; Kinage, Anil K. (Organic & Biomolecular Chemistry, 2025)
The organocatalyzed one-pot Michael addition reaction of propanal to isatylidene malononitriles remains largely unexplored due to challenges in controlling the reaction and preventing side processes such as aldol condensation, self-aldolization, and 1,3-dipolar cycloaddition. In this study, we introduce a one-pot methodology for the synthesis of 3 `-alkyl spiro[2H-pyran-3,4 `-indoline] via an organocatalyzed Michael addition of simple propanal to isatylidene malononitrile derivatives, which are generated in situ from isatin derivatives and malononitrile. Subsequent reduction of the Michael adduct with NaBH4 leads to the target product with high efficiency under mild conditions. This strategy offers several advantages, including environmental sustainability, high to excellent yields, shorter reaction times, cost-effectiveness, and ease of implementation.

Efficient synthesis of 3,3′-Spirooxindole γ-Butyrolactone via Rongalite-mediated domino reductive aldol and spiro-lactonization reactions - Chaudhari, Suryakant S.; Nichinde, Chandrakant B.; Patil, Baliram R.; Girase, Amardipsing S.; Kinage, Anil K. (ChemistrySelect, 2025)
In this study, we develop a novel methodology involving rongalite-mediated domino reductive/aldol reaction, followed by spiro-lactonization of 2-oxoindolin-3-ylidene acetates/malonates in presence of base to synthesis of 3,3 `-spirooxindole gamma-butyrolactone. The detail study, such as effect of solvent, effect of different base and substrate has been carried out. Scale up of this methodology is also done. Sodium hydroxymethanesulfinate dihydrate (rongalite) concurrently has a dual role in this context; it acts as a reducing agent as well as C1 synthon. This approach offers several advantages, such as being metal- and catalyst-free, involving a simple reaction protocol, having a wide substrate scope, using water as a green solvent, and providing good to excellent yields of the products under mild reaction conditions.
Keywords: (+/-) Coixspirolactam A & [3; 3 `-spirooxindole gamma-butyrolactone]; Domino reductive/aldol/spiro-lactonization; Good step economy; Rongalite as reductant & C1 synthon; Water as a green solvent

Evaluation of reaction kinetics for chemoselective hydrogenation of citral for intensification of citral intermediates using copper-based catalysts - Debtirtha, Banik; Kinage, Anil K.; Vasireddy, Satyam Naidu (Indian Chemical Engineer, 2025)
Citral intermediates’ formation kinetics is studied using non-noble metal catalyst (Cu/SiO2) to evaluate catalyst performance characteristics via chemoselective hydrogenation of citral. The catalyst is synthesised by the precipitation method and characterised using XRD, FESEM and BET surface area analyser. Hydrogenation experiments are carried out using an Autoclave reactor in the temperature range of 80–120°C, pressure range of 10–50 bar and for catalyst loadings of 0.5, 1 and 1.5 g. The intermediates product distribution comprises aldehyde and alcohol formation such as citronellal, nerol and citronellol formation. The performance of the Cu/SiO2 catalyst is evaluated using the parameters such as citral conversion, citronellol selectivity and yield as 96.96%, 95.30% and 92.30%, respectively under optimal conditions of 50 bar, 120°C and 1 g catalyst for the reaction time of 100 min. The absence of internal and external mass transfer limitations is verified using the Carberry number and Weisz-Prater modulus criterion. The intrinsic kinetics of the gas–liquid phase hydrogenation of citral is determined using the Langmuir–Hinshelwood-Hougen-Watson (LHHW) model for citral intermediates formation. The reaction kinetic parameters show that citronellol formation favours by the nerol route compared to citronellal conversion.

Rongalite-promoted self-dimerization of 3-acylidene-2-oxindoles: a diastereoselective route to synthesis of bispirooxindoles - Chaudhari, Suryakant S.; Nichinde, Chandrakant B.; Patil, Baliram R.; Girase, Amardipsing S.; Kaulage, Sandeep H.; Kinage, Anil K. (Organic & Biomolecular Chemistry, 2025)
A facile and efficient one-pot rongalite-mediated self-dimerization of 3-acylidene-2-oxindoles has been developed for the diastereoselective synthesis of highly functionalized dispirocyclopentanebisoxindoles. The reaction proceeds via a domino sequence involving intermolecular Michael addition followed by intramolecular aldol cyclization under basic conditions. Rongalite, an inexpensive and readily available reagent (similar to\$0.03 per g), plays a crucial role in promoting the transformation, offering significant advantages such as operational simplicity, step economy, scalability to gram-scale synthesis, and potential for post-functionalization. This methodology provides an efficient route to structurally complex oxindole frameworks with high stereocontrol, demonstrating broad synthetic utility.

Sequential nitro-michael addition and reductive cyclization cascade reaction for diastereoselective synthesis of multifunctionalized 3,3′-pyrrolidinyl-spirooxindoles - Nichinde, Chandrakant B.; Bhati, Meema; Girase, Amardipsing S.; Patil, Baliram R.; Chaudhari, Suryakant S.; Gamidi, Rama Krishna; Joshi, Kavita; Kinage, Anil K. (European Journal of Organic Chemistry, 2025)
In this investigation, we elucidated, one-pot two stage efficient synthesis of multifuctionalized spiro[oxindole -3,3 `-pyrrolidine]. The methodology proceeds via organocatalyzed nitro-Michael addition reaction between indolylidenecyanoesters and nitroalkanes to formed nitro-Michael adduct which transformed into multifunctionalized 3,3 `-pyrrolidinyl-spirooxindoles by metal catalyzed reductive cyclization cascade. DFT investigations were conducted to elucidate the mechanism underlying the preferential reduction of the nitro group, with subsequent attack on the nitrile and ester groups remain inert throughout the reaction process. The approach is operationally simple, easily scalable, exhibits compatibility with readily accessible starting material and catalysts, thereby emphasizing cost-effectiveness.
Keywords: 3 `-pyrrolidinyl spirooxindoles; DFT study for regioselective cyclization; Diastereoselective 3; organocatalysis; Pd/C catalysed partial reductive spirocyclization

Reaction kinetics for dehydrogenation of decahydroquinoline to quinoline for hydrogen generation - Bagwan, Farahanaz M.; Dadkar, Sarthak S.; Kinage, Anil K.; Vasireddy, Satyam Naidu (Chemical Engineering & Technology, 2026)
Catalytic dehydrogenation of decahydroquinoline (DHQ) to quinoline is a promising pathway for hydrogen release in liquid organic hydrogen carrier systems. In this work, solvent-free DHQ dehydrogenation over Pd/Al2O3 is systematically investigated to evaluate hydrogen release performance and reaction kinetics. High DHQ conversion (83.9%) and degree of dehydrogenation (82.7%) are achieved at optimal reaction conditions. A power-law kinetic model based on a simplified reaction mechanism is developed and simulated using a Markov Chain Monte Carlo (MCMC) approach for estimation of rate constants and validation of concentration profiles with experimental data. The apparent activation energies are determined to be 45.85 kJ/mol for DHQ to 5,6,7,8-tetrahydroquinoline (bz-THQ) and 185.43 kJ/mol for bz-THQ to quinoline formation, identifying latter as the rate-limiting step. This framework provides mechanistic insight and supports the potential of DHQ as an efficient hydrogen carrier.
Keywords: Decahydroquinoline (DHQ); degree of dehydrogenation; Dehydrogenation; rate-limiting step; Reaction kinetics; Weisz-Prater criterion

Thiophenol-mediated metal-free chemoselective conjugate reduction strategy for 3-alkylidene oxindoles - Patil, Baliram R.; Nichinde, Chandrakant B.; Girase, Amardipsing S.; Chaudhari, Suryakant S.; Kinage, Anil K. (RSC Advances, 2026)
A mild and metal-free thiophenol-mediated chemoselective conjugate reduction of 3-alkylidene oxindoles via a thiol-ene-type Michael addition was effectively carried out. Thiophenol as an efficient reductant is used in DMSO, and the transformation proceeds without the need for metal catalyst, external hydrogen source, or harsh reagents. The reaction displays a broad substrate scope, accommodating both electron-donating and electron-withdrawing substituents, and delivers 3-alkyloxindoles in high yields with excellent beta-selectivity. This sustainable and operationally simple method unveils a distinct thiol-mediated reduction mechanism, providing a green and versatile approach for accessing reduced oxindole derivatives and related Michael acceptors.